THE USE OF COLORFUL SEMANTICS TO IMPROVE SENTENCE CONSTRUCTION IN WRITING SENTENCES AMONG YEAR FOUR PUPILS - Kee Li Li; Tay Jie Yee (Journal of English Education, 2017)
This action research was set out to develop pupils’ writing skill using colorful semantics. The main two objectives established from the outset were to develop pupils’ sentence construction and improve my teaching practice in sentence construction teaching respectively. As the researcher, I conducted this classroom action research to 31 pupils which comprised 17 males and 14 females of Year 4J of SJK(C) Cheng Siu 2 in Malaysia. The data was gathered through pre- writing test and post- writing test, pupils’ work as well as teacher’s reflective journal. Over the course of four weeks, I introduced colorful semantics to my pupils in accordance to the sequence of ‘who’, ‘what doing’, ‘what’ and ‘where’. As can be induced from the findings, colorful semantics was statistically significant to pupils’ sentence construction through the enhancement of pupils’ ability to understand words of each sentence part and also to write sentence in the correct order. The findings also depicted that utilization of colorful semantics improved my teaching practice to become a reflective, passionate, and motivational teacher. Therefore, the positive results warrant further research into colorful semantics with suggestions to integrate Information, Communication, and Technology (ICT) into lessons and expose pupils to more sentence types.